- Peningkatan Komunikasi Pelayanan Publik Melalui Pendampingan SKHPN di BNN Provinsi Bali: Peningkatan Komunikasi Pelayanan Publik Melalui Pendampingan SKHPN di BNN Provinsi Bali - Yunita, Eka; Basmantra, Ida Nyoman (Program Studi Ilmu Komunikasi Universitas Pamulang, 2026)
This community service activity was carried out at the Provincial National Narcotics Agency in Bali, focusing on improving public service communication through assistance in the process of obtaining a Narcotics Examination Result Certificate. The activity was motivated by the low level of digital literacy among the public in accessing the service online via the official booking application, which often caused delays and procedural errors. The implementation involved direct assistance at the service counter and remote assistance via WhatsApp, supported by written guidelines and digital brochures. The aim was to help the public understand the registration process, online payment procedures for non-tax state revenue, and the examination process. The results showed improved public understanding of digital service procedures, fewer technical errors, and more efficient service time. In conclusion, educational, adaptive, and responsive assistance proved effective in bridging the digital literacy gap and enhancing public service communication in the provincial government’s narcotics examination services. Keywords: public service communication, drugs test certificate, digital literacy